Salary cuts and competitiveness - Michael Haliassos (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
There is a prevalent view outside Greece that promotion of competitiveness is tantamount with price reductions for Greek goods and services. Massive horizontal salary cuts appear, at first, to promote competitiveness by reducing unit labor costs and to reduce fiscal deficits by reducing the wage bill of the public sector. Upon closer look, however, horizontal salary cuts have been much greater than needed for Greek competitiveness, providing an alibi vis a vis the Troika for reforms that are still to be implemented, but at the same time undermining both competitiveness and the potential to reduce public debt through sustainable development.
urn:nbn:de:hebis:30:3-299611
Keywords: 330; Greek economic crisis; productivity; structural reforms